Analysis of genetic diversity of Borrelia burgdorferi sensu lato and Borrelia miyamotoi across Central and Eastern Europe using multilocus sequence typing (MLST) in range of Slovakia and data from the MLST database with focus on Central and Eastern Europe - Morávková, Veronika (Jihočeská univerzita, 2022)
The study was based on tick collection, DNA extraction, PCR amplification, sequencing and computational analyses of Borrelia burgdorferi sensu lato and B. miyamotoi. The study included evaluation on the prevalence of Borrelia burgdorferi sensu lato and B. miyamotoi in Ixodes ricinus ticks across the Slovak Republic based on the collection of ticks from 2017. The spirochetes were further classified into genospecies as well as sequence types (ST) according to MLST method by amplifying and sequencing eight housekeeping genes. Subsequently, population-genetic relationships of Borrelia tick-borne pathogens across Central and Eastern Europe were analysed.
Analysis of genetic diversity of Borrelia burgdorferi sensu lato and Borrelia miyamotoi across Central and Eastern Europe using multilocus sequence typing (MLST) in range of Slovakia and data from the MLST database with focus on Central and Eastern Europe
Keywords: Borrelia afzelii; Borrelia garinii; Borrelia burgdorferi sensu stricto; Borrelia miyamotoi; PCR; MLST; MLSA; Ixodes ricinus; sequence type; genetic diversity; Slovak Republic; Slovakia; population-genetic analysis; Lyme borreliosis; Lyme disease; relapsing fever; Borrelia afzelii; Borrelia garinii; Borrelia burgdorferi sensu stricto; Borrelia miyamotoi; PCR; MLST; MLSA; Ixodes ricinus; sequence type; genetic diversity; Slovak Republic; Slovakia; population-genetic analysis; Lyme borreliosis; Lyme disease; relapsing fever